Intelligent Functions Development on Autonomous Electric Vehicle Platform - Ruxin WANG; Raivo SELL; Anton RASSOLKIN; Tauno OTTO; Ehsan MALAYJERDI (Journal of Machine Engineering)
Autonomous driving is no longer just an idea of technology vision instead a real technical trend all over the world. The continuing development to a further level of autonomy requires more on mobile robots safety while bringing more challenges to human-vehicle interaction. A robot autonomous vehicle (AV) as a research platform operates an experimental study on human-AV-interaction (HAVI) and performs a novel method for mobile robot safety assurance. Not only autonomous driving technology itself but human cognition also performs an essential role in how to ensure better autonomous mobile robot safety. A Wizard-of-Oz experiment in the university combing a survey-based study indicates public attitudes towards driverless robot vehicles. HAVI experiment have been carried through light patterns designed for experiment. This paper presents an attempt to investigate humans’ acceptance and emotions as well as a validation to bring the mobile robot vehicle to a high-level autonomy.